Directional transport of droplets impacting on superhydrophobic opening triangular groove surfaces. Issue 1 (1st June 2022) - Li, Yunlai; Lu, Chenguang; Liu, Yahua
Abstract: Directional droplet transport is of great importance to various processes including heat transfer, water harvesting and microfluidics. Here, a facile superhydrophobic opening triangular groove surface was proposed, and the directional transport behavior of droplets impacting on the surface was observed. The results show that the essence of the directional transport on the opening triangular groove surface can be attributed to the interaction between the impinging droplet and the groove sidewall, and the directional transport distance is regulated by the contact area during the interaction. Further, by controlling the depth of triangular groove, the triangular opening angle, the impacting point position and the Weber number, the contact area between the droplet and the groove sidewall during the interaction can be changed, leading to the variation of directional transport distance. This study provides a new method for directional droplet transport on superhydrophobic surfaces and offers more options for the manipulation of droplet behavior.